Community Pharmacists’ Perspectives toward Continuing Professional Development: A Qualitative Study - Hjazeen, Rima (Jordan Journal of Pharmaceutical Sciences, 2023)
Objectives: This study’s principal aim was to investigate community pharmacists’ views of continuing professional development (CPD) and to explore pharmacists’ perceptions of the most common facilitators and barriers to participation in continuing education (CE). Methods: A series of seven focus group sessions were undertaken with groups of four to seven community pharmacists. Focus group transcripts were thematically analyzed using a qualitative data analysis method. Results: Four key themes were identified: (1) community pharmacists’ attitudes toward CPD; (2) perceived motivating factors for CPD; (3) experienced barriers to CPD; (4) and potential strategies for improving pharmacists’ CPD. Conclusion: Practicing pharmacists need support now, and changes to undergraduate education are warranted to keep abreast of current developments and changes to practice. Despite limitations, the distinctive nature of this study would have a valuable contribution to the field of professional development. It can inform theory, policy, and practice relating to pharmacists’ CPD at both a professional level and governmentally, helping the relevant parties make informed decisions.